2020
DOI: 10.1007/s40268-020-00303-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Types of Pathological Upper Gastrointestinal Endoscopy Findings in Clinically Healthy Individuals

Abstract: Background and objective Beyond its application for diagnostics in patients, esophagogastroduodenoscopy (EGD) is used to assess gastrointestinal drug effects in clinical trials, where the interpretation of any pathological findings depends on the respective background variability. The objective of this analysis was to characterize the occurrence of pathological findings in the upper gastrointestinal tract in symptom-free healthy individuals. Methods A baseline EGD was performed in clinically healthy individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…12 On the other hand, Scheidl et al, 2020 which included younger patients the mean age was 32 years. 13 Regarding to gender, our study showed that there is slight predominance of female gender patients in percent of 50.1%, versus 49.9% were males.…”
Section: Discussionmentioning
confidence: 55%
“…12 On the other hand, Scheidl et al, 2020 which included younger patients the mean age was 32 years. 13 Regarding to gender, our study showed that there is slight predominance of female gender patients in percent of 50.1%, versus 49.9% were males.…”
Section: Discussionmentioning
confidence: 55%